The book of wonder - Polo, Marco, 1254-1323? (Parkstone Press International, 2015)
The most renowned travel story of the Middle Ages has never lost its allure. A story of true wonder, Marco Polo's experiences as well as the reported myths, transport us to the heart of Central Asia, China, Indochina, and the Indian Ocean. The original manuscripts were accompanied with illustrations realised from the few descriptions made by the traveller. Following in the footsteps of Marco Polo, the various illustrations found here will send the reader on the path to discovering the distant lands as we know them today.